Developing relationships that matter : educator experiences of delivering relationship and sexuality education in Aotearoa/New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Manawatū, Aotearoa/New Zealand - Robertson, Carey (Massey University, 2023)
Sexuality education is a contested space, wherein a variety of stakeholders and affective forces converge and respond to an adolescent sexuality that is configured as a social problem within dominant knowledge systems and power relations. Young women and girls are articulated as especially risky and at-risk, becoming anticipated burdens that threaten to trouble neoliberal capitalism and its postfeminist sensibilities. A tension emerges between the disposable bodies of transnational capitalism and the assumption that gender equality has already been achieved, playing out in the sexualised adolescent caricatures consumed within modern media consumption practices and the everyday sexual violence that inequitably targets women and girls. Manifesting through the author’s own earned experiences and the particular ways through which gendered violence informs the standpoint of this project, the process of reading through theory becomes constitutive of the doing of this research. Evolving into a feminist posthuman approach to mapping the affective flows that produce sexuality education capacities in Aotearoa/New Zealand through a close reading of theory, policy, and six educator narratives, the latest changes to sexuality education policy are interrogated, making visible the affective forces that work to territorialise sexuality education praxis. The focus of analysis is on the possibilities for building relationships that matter with young people, by centring the relational through ethical engagement with the co-constructed narratives of educators. Connecting these narratives through theory to the broader social power relationships in which they are embedded, the gendered and colonised bodies of neoliberal capitalism emerge as hidden in plain sight, while moral, professional, and institutional barriers emerge through feelings of fear and shame as individualising forces that obstruct the relational within the context of sexuality education. Bringing the voices of educators together in collaboration, horizons of hope are also identified - with student voice, acknowledgement of the embodied knowing of young people, activism that works to increase the value of creating space for students to connect in processes of becoming (political), teacher education, and a dis-identification with heteronormative practices emerging as possibilities for troubling the (still) hidden power relationships that produce relational capacities within institutional spaces.
Keywords: 520102 Educational psychology